Facetas de burocracia - Valdir Melo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– It is useful to acknowledge at least four facets of bureaucracy. And bureaucratic management has a few general characteristics, such as professionalism of the officers, organizational subdivision and a complex system of registers. Administrative procedures aim at effectiveness by applying the principle of division of labor, as well as by preventing the disadvantages of people's spontaneity and informality to productive purposes. As to a whole state, it is feasible to render flexible many bureaucratic procedures as well as to extinguish bureaucratic malfunctions to a large extent. But this requires employment of resources along several years and several government terms.
Keywords: D73; A13; B40; 330; bureaucracy; bureaucratic management; administrative procedure